Evaluasi Kualitas Sensoris dan Fisikokimia Mi Basah Sorgum (Sorghum bicolor L. Moench) sebagai Pangan Fungsional - Prabawa, Sigit; Zoelnanda, Anisya; Anam, Choiroel; ., Samanhudi (Jurnal Teknologi Hasil Pertanian, 2023)
Sorghum contains nutrients and has the potential to become functional food. The purpose of the research is to know sensory, physicochemistry, and it’s potency as functional food of noodle made from wheat flour substituted by sorghum flour from Numbu and Super 2 variety. The comparison of wheat and sorghum flour used in this research are 35:65; 50:50 ; and 65:35. This research used sorghum flour used to make the noodle comes from two different variety, Numbu and Super 2. Anova was used to analyze the difference between groups and DuncanMultiple Range test for within groups. Sensory analysis was done using 40 untrained panelists shows that there was significant difference based on formulation on the color, aroma, flavor, texture, elasticity, and overall parameters, but there was no difference based on sorgum variety. Noodle samples with higher proportion of sorghum has lower score. The highest sensory value was obtained by wet noodle made from 35% soghum fluor from Numbu variety. Wet noodle resulting from wheat flour and sorghum flour have elongation score range from 10.5833–40.0000%. Water content of the noodle samples range from 33.3731–38.4184%, ash content range from 0.4799–0.8670%, protein content range from 6.2080–8.1109%; fat content range from 1.1250–2.5684%; meanwhile carbohydrate contain range from 51.9081–57.1975%. The noodle has potential to be functional food product due to high antioxidant activity (84.32–89.12%) and the dietary fiber content (2.540–4.370%).